Ternary composite based resistive gas sensor
Patent Information
- Application Number
- KR1020260066429
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-04-14
- Filing Date
- 2026-04-13
- Publication Date
- 2026-10-21
Smart Images

Figure PAT00002_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to an ammonia detection sensor based on a ternary complex, and more specifically, to an ammonia gas detection sensor utilizing a detection layer comprising a ternary complex. Background Technology
[0002] Ammonia (NH3) is the most common chemical manufacturing material on Earth and is an essential raw material for the production of pharmaceuticals, refrigerants, fertilizers, and various nitrogen chemicals. However, ammonia exists as a gas at room temperature and has strong alkalinity, which damages equipment such as metal and concrete. Furthermore, due to its high volatility, if leaked from damaged equipment, it rapidly diffuses into the atmosphere, causing foul odors and acid rain.
[0003] In addition, ammonia gas is an irritating gas harmful to the human body. According to the U.S. Occupational Safety and Health Administration (OSHA), exposure to ammonia at concentrations of 35 ppm or higher for more than 15 minutes can cause irritation to the eyes, nose, and throat, and prolonged exposure may cause respiratory discomfort. Furthermore, exposure to ammonia at concentrations of 300 ppm to 500 ppm or higher can cause acute health risks such as acute poisoning, eye pain, difficulty breathing, chemical burns, and suffocation. Therefore, high-performance ammonia detection sensors are being researched to prevent ammonia leakage and exposure to the human body.
[0004] In conventional ammonia sensors, metal oxides with high reactivity to ammonia gas, such as tin oxide (SnO2), tungsten oxide (WO3), and zinc oxide (ZnO), or metal oxides with added catalytic metals are used as ammonia detection materials. However, ammonia sensors using metal oxides require operation at high temperatures to induce a reaction with ammonia gas, resulting in high energy consumption. Additionally, they react with gases other than ammonia, leading to low selectivity and sensitivity, and their stability is degraded by temperature and humidity, making them difficult to use indoors.
[0005] Therefore, there is a need for new ammonia sensing materials with excellent selectivity and reproducibility even at room temperature, and ammonia sensing sensors utilizing such materials. The problem to be solved
[0007] In order to solve the aforementioned problems, the first objective of the present invention is to provide an ammonia detection sensor having a detection layer formed therein capable of detecting ammonia.
[0008] The second objective of the present invention is to provide a method for manufacturing the ammonia detection sensor of the first objective. means of solving the problem
[0009] To solve the above-mentioned first problem, the present invention provides an ammonia sensing sensor comprising an electrode having a sensing layer formed thereon, the sensing layer comprising a ternary complex of a transition metal dichalcogenide, a conductive polymer, and MXene.
[0010] To solve the above second problem, the present invention provides a method for manufacturing an ammonia sensing sensor by coating a ternary complex of a transition metal dichalcogenide, a conductive polymer, and MXene onto an electrode to form a sensing layer on the electrode. Effects of the invention
[0011] The ammonia sensing sensor of the present invention is formed with a sensing layer comprising a transition metal dichalcogenide, which is an ammonia sensing material, a conductive polymer that imparts charge mobility, and a MXene that enhances sensitivity, and can detect ammonia through a change in resistance caused by the reaction between the sensing layer and ammonia gas.
[0012] In addition, the ammonia detection sensor of the present invention has a fast reaction speed with ammonia gas and excellent sensitivity even at room temperature, and maintains detection performance even after repeated cycles, so it can be utilized in various fields.
[0013] In addition, the ammonia detection sensor of the present invention exhibits excellent linearity between ammonia concentration and response, allowing for rapid determination of the exposed ammonia concentration. Brief explanation of the drawing
[0015] Figure 1 is a schematic diagram illustrating the principle of the ammonia detection sensor of the present invention. FIG. 2 is a schematic diagram showing a method for preparing a transition metal dichalcogenide, a conductive polymer, and a MXene composite of the present invention. Figure 3 is a graph showing the results of XRD analysis of the crystal structure of the transition metal dichalcogenide, conductive polymer, and MXene composite of the present invention. Figure 4 is an image showing the results of SEM analysis and EDS mapping of the microstructure of the transition metal dichalcogenide, conductive polymer, and MXene composite of the present invention. Figure 5 is an image showing the results of analyzing the structure of an ammonia sensing sensor comprising a transition metal dichalcogenide, a conductive polymer, and a MXene complex of the present invention using FESEM. FIG. 6 is a schematic diagram showing a gas detection device comprising an ammonia detection sensor comprising a transition metal dichalcogenide, a conductive polymer, and a MXene composite of the present invention. Figure 7 is a graph showing the results of analyzing the ammonia gas detection capability of an ammonia detection sensor comprising a transition metal dichalcogenide, a conductive polymer, and a MXene complex of the present invention. Figure 8 is a graph showing the results of a comparative analysis of the ammonia gas detection performance of an ammonia detection sensor comprising a transition metal dichalcogenide, a conductive polymer, and a MXene complex of the present invention. Figure 9 is a graph showing the results of a comparative analysis of the performance of an ammonia sensing sensor comprising a transition metal dichalcogenide, a conductive polymer, and a MXene composite of the present invention. Figure 10 is a graph showing the results of analyzing the selectivity of an ammonia sensing sensor comprising a transition metal dichalcogenide, a conductive polymer, and a MXene complex of the present invention. Specific details for implementing the invention
[0016] Hereinafter, the present invention will be described in detail with reference to embodiments and drawings so that those skilled in the art to which the present invention pertains can easily implement it. The embodiments of the present invention are provided to more completely explain the present invention to those with average knowledge in the art. Accordingly, the embodiments of the present invention may be modified in various different forms, and the scope of the present invention is not limited to the embodiments described below but may be embodied in other forms.
[0017] Throughout the specification of the present invention, when a part is described as "comprising" a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.
[0018] Throughout the specification of the present invention, "steps" or "steps of" do not mean "steps for."
[0019] The term "transition metal dichalcogenide (TMD)" used throughout the specification of the present invention refers to a compound in which a transition metal (M: Mo, W, etc.) and a chalcogen (X: S, Se, Te) are bonded in the form of MX2, and is a nanomaterial having a two-dimensional structure similar to graphene, which electrically possesses various properties such as semiconductors and conductors.
[0020] The term "MXene" used throughout the specification of the present invention refers to a compound in the form of MXT, in which a transition metal (M: Ti, Mo, Nb, V, etc.), a nonmetal (X: C or N), and a surface functional group (T: -OH, -O, -F, etc.) are combined, and is a nanomaterial having a two-dimensional structure similar to graphene, having high electrical conductivity and hydrophilicity.
[0022] Examples
[0024] The present invention provides an ammonia detection sensor comprising a detection layer containing a ternary complex. Specifically, the ammonia detection sensor comprises an electrode and a detection layer formed on the electrode, wherein the detection layer may comprise a ternary complex of a transition metal dichalcogenide, a conductive polymer, and MXene. The detection layer containing the ternary complex may change resistance upon reacting with ammonia gas, and ammonia may be detected through the change in resistance. Specifically, the transition metal dichalcogenide included in the detection layer may provide an adsorption active site for ammonia gas, the conductive polymer may form a charge transfer path between the transition metal dichalcogenide and the MXene, and the MXene may improve gas adsorption capacity by enhancing electron mobility and active surface area, and provide an effective path for charge transfer. Furthermore, the sensitivity of the ammonia detection sensor may be enhanced by the charge transfer path between the transition metal dichalcogenide and the MXene formed by the conductive polymer, and long-term stability may be improved as the charge transfer path becomes stable.
[0025] In the ammonia sensing sensor above, the electrode may be any conductive metal electrode that is not deformed by the ternary composite without limitation, and specifically, may be an electrode of one or more metals selected from the group consisting of silver (Ag), gold (Au), platinum (Pt), palladium (Pd), ruthenium (Ru), and alloys thereof. Additionally, the electrode may be an electrode formed on a support, or an electrode formed on the support without limitation of shape and pattern. The support may be made of glass, silicon, ceramic, or polymer material, but is not limited thereto. The electrode may include comb-shaped fingers and may be an interdigital electrode in which the comb-shaped fingers are arranged to interlock with each other, may be a nanodot electrode arranged in the form of nano-sized dots, or may be a nanowire network electrode or a nanotube network electrode in which nano-structured electrodes are formed like a mesh, but is not limited thereto.
[0026] In the ammonia detection sensor above, the detection layer can be formed on the electrode with a thickness of 200 nm to 1000 nm, specifically with a thickness of 600 nm to 800 nm. If the thickness of the detection layer is less than 200 nm, it may be easily damaged or misdetected as another gas, and if it exceeds 1000 nm, the response speed and sensitivity may decrease.
[0027] The ternary composite included in the sensing layer of the ammonia sensing sensor may be a composite comprising 70 wt% to 94 wt% of the transition metal dichalcogenide, 1 wt% to 10 wt% of the conductive polymer, and 5 wt% to 20 wt% of the MXene, and specifically, may be a composite comprising 78 wt% to 90 wt% of the transition metal dichalcogenide, 2 wt% to 6 wt% of the conductive polymer, and 8 wt% to 16 wt% of the MXene. In the ternary composite, if the content of the transition metal dichalcogenide is less than 70 wt%, the adsorption site of the ammonia gas between the sensing layer and the ternary composite is reduced, which may reduce sensitivity, and if it exceeds 94 wt%, other gases may be falsely detected. In the above ternary composite, if the content of the conductive polymer is less than 1 wt%, the charge transfer path is reduced, which may decrease the reaction rate, and if it exceeds 10 wt%, noise may increase or other gases may be falsely detected. In the above ternary composite, if the content of the MXene is less than 5 wt%, the reaction rate may decrease, and if it exceeds 20 wt%, the change in resistance is negligible, which may decrease the detection efficiency.
[0028] The ternary composite included in the sensing layer of the ammonia sensing sensor may include one or more transition metal dichalcogenides selected from the group consisting of molybdenum disulfide (MoS2), molybdenum diselenide (MoSe2), tungsten disulfide (WS2), and tungsten diselenide (WS2), and specifically may include molybdenum diselenide (MoSe2). Additionally, the ternary composite may include one or more conductive polymers selected from the group consisting of polyaniline (PANI), polypyrrole (PPy), polythiophene (PT), and mixtures thereof, and specifically may include polyaniline (PANI). In addition, the above ternary complex is titanium carbide MXene (Ti3C2T x ), niobium carbide MXene (Nb2CT x ), vanadium carbide MXene (V2CT x ) and molybdenum carbide MXene (Mo2CT x It may include one or more MXenes selected from the group consisting of ), specifically titanium carbide MXene (Ti3C2T x It can be.
[0029] The above ammonia detection sensor may have ammonia gas selectivity, specifically ammonia gas selectivity at room temperature, and may have ammonia gas selectivity in a mixed gas including ammonia (NH3), carbon dioxide (CO2), methane (CH4), nitrogen dioxide (NO2), etc.
[0030] The above ammonia detection sensor may have a detection value (R) of 88.0 to 6500.0, specifically, a detection value (R) of 88.0 to 6500.0 at room temperature, and preferably, a detection value (R) of 88.0 to 6500.0 at room temperature under conditions where 1000 ppm of ammonia gas is present. The above detection value (R) can be calculated using the following formula 1.
[0031] [Formula 1]
[0032]
[0033] R in the above calculation formula 1 o can be the initial resistance value of the sensor in air, and R g may be the resistance value of the sensor in an environment where the above ammonia gas is present.
[0034] The above ammonia detection sensor may have a response time of 4.0 S to 20.0 S at which it reaches 90% of the final output signal under conditions where ammonia gas is present, specifically, the response time may be 4.0 S to 20.0 S under conditions where 0.1 ppm to 1000 ppm of ammonia gas is present, and preferably, the response time may be 4.0 S to 18.0 S at room temperature under conditions where 0.1 ppm to 1000 ppm of ammonia gas is present.
[0035] The above ammonia detection sensor may have a recovery time of 15.0 S to 35.0 S at which it reaches 90% of the maximum resistance change under conditions where it is exposed to and then removed from ammonia gas, specifically, the recovery time may be 15.0 S to 35.0 S under conditions where it is exposed to and then removed from ammonia gas of 0.1 ppm to 1000 ppm, and preferably, the recovery time may be 18.0 S to 35.0 S at room temperature under conditions where it is exposed to and then removed from ammonia gas of 0.1 ppm to 1000 ppm.
[0036] The above ammonia detection sensor may have a Limit of Detection (LOD) of 0.6 ppm or higher, and specifically, the limit of detection concentration of ammonia gas at room temperature may be 0.6 ppm or higher.
[0037] The above ammonia detection sensor can detect ammonia gas of 1 ppm to 1000 ppm, and specifically, can detect ammonia gas of 1 ppm to 1000 ppm at room temperature.
[0039] Figure 1 is a schematic diagram illustrating the principle of the ammonia detection sensor of the present invention.
[0040] Referring to FIG. 1, the ammonia sensing sensor of the present invention shows that the ammonia gas reacts with the sensing layer formed on the electrode and the ammonia gas is adsorbed on the sensing layer, and the adsorbed ammonia gas induces a change in electron density within the ternary complex contained in the sensing layer, thereby allowing the resistance value to change sensitively.
[0042] In addition, the present invention provides a method for manufacturing an ammonia sensing sensor comprising a sensing layer including a ternary composite. Specifically, the ammonia sensing sensor may be manufactured by preparing a ternary composite, adding and stirring the ternary composite in a solvent to prepare a ternary composite dispersion solution, and then coating the ternary composite dispersion solution onto an electrode. The ternary composite may be a composite comprising a transition metal dichalcogenide, a conductive polymer, and MXene. The content of the ternary composite in the ternary composite dispersion solution may be 0.1 wt% to 10.0 wt% relative to the total dispersion solution, and specifically, may be 0.5 wt% to 5.0 wt% relative to the total dispersion solution.
[0043] The ammonia detection sensor manufactured by the above manufacturing method, the composition, performance, and effects of the sensor, etc., are identical to the description of the ammonia detection sensor, so the above content is adopted by reference. Furthermore, the ternary composite, the composition, performance, and effects of the composite, etc., are identical to the ternary composite included in the detection layer of the ammonia detection sensor, so the above content is adopted by reference. Additionally, regarding the electrode, the composition, performance, and effects of the electrode, etc., are identical to the electrode of the ammonia detection sensor, so the above content is adopted by reference.
[0044] The above ternary composite can be prepared by preparing transition metal dichalcogenide nanoflowers and MXene, adding and stirring the transition metal dichalcogenide nanoflowers or MXene, respectively, into a solvent to prepare a transition metal dichalcogenide dispersion solution or a MXene dispersion solution, then adding and stirring a conductive polymer precursor solution dropwise to a mixed solution of the transition metal dichalcogenide dispersion solution and the MXene dispersion solution, and filtering the stirred solution to separate the ternary composite. The stirred solution may be a solution in which 20 wt% to 50 wt% of the transition metal dichalcogenide dispersion solution, 20 wt% to 50 wt% of the MXene dispersion solution, and 10 wt% to 40 wt% of the conductive polymer precursor solution are stirred. In the above-mentioned transition metal dicalconide dispersion solution, the content of the transition metal dicalcogenide nanoflower may be 0.1 wt% to 10.0 wt% relative to the total dispersion solution, and specifically, 1.0 wt% to 5.0 wt% relative to the total dispersion solution. In the above-mentioned MXene dispersion solution, the content of the MXene may be 0.1 wt% to 10.0 wt% relative to the total dispersion solution, and specifically, 1.0 wt% to 5.0 wt% relative to the total dispersion solution.
[0045] The above transition metal dichalcogenide nanoflower can be prepared by mixing a transition metal precursor solution and a chalcogen precursor solution to form a mixed solution, reacting the solution at a high temperature, centrifuging the high-temperature reacted mixed solution to separate the transition metal dichalcogenide nanoflower precipitate, and then vacuum drying and grinding the precipitate. The concentrations of the transition metal precursor solution and the chalcogen precursor solution may be 0.1 M to 1.0 M, specifically 0.15 M to 0.70 M. If the concentration of the transition metal precursor solution and the chalcogen precursor solution is less than 0.1 M, nucleation may be insufficient, resulting in insufficient crystal formation; if it exceeds 1.0 M, side reactions increase, thickness increases, and the response speed may decrease. The mixed solution of the transition metal precursor solution and the chalcogen precursor solution may be a solution in which 50 wt% to 80 wt% of the transition metal precursor solution and 20 wt% to 50 wt% of the chalcogen precursor solution are mixed, specifically, a solution in which 60 wt% to 70 wt% of the transition metal precursor solution and 30 wt% to 40 wt% of the chalcogen precursor solution are mixed. If the transition metal precursor solution is less than 50 wt% or the chalcogen precursor solution is greater than 50 wt%, the metal deficiency defects of the prepared transition metal dichalcogenide may increase, thereby reducing long-term stability, and if the transition metal precursor solution is greater than 80 wt% or the chalcogen precursor solution is less than 20 wt%, the chalcogen deficiency defects may increase, thereby reducing ammonia gas selectivity.
[0046] The above transition metal precursor solution may be a solution of one or more transition metal precursors selected from the group consisting of sodium molybdate (Na2MoO4), ammonium tetrathiomolybdate ((NH4)2MoS4), molybdenum trioxide (MoO3), molybdenum pentachloride (MoCl5), sodium tungstate (Na2WO4), tungsten trioxide (WO3), tungsten hexachloride (WCl6), and mixtures thereof. The above chalcogen precursor solution may be a solution of one or more chalcogen precursors selected from the group consisting of hydrogen sulfide (H2S), carbon disulfide (CS2), sulfur (S) powder, hydrogen selenide (H2Se), selenium dioxide (SeO2), selenium (Se) powder, and mixtures thereof.
[0047] The above MXene can be prepared by introducing and stirring the MAX phase into an acidic solvent to prepare a suspension, washing the suspension to neutralize it, centrifuging the washed suspension to separate the generated MXene precipitate, and vacuum drying the precipitate. The acidic solvent may be hydrofluoric acid (HF) or a mixed solvent of lithium fluoride (LiF), sodium fluoride (NaF), potassium fluoride (KF), and hydrochloric acid (HCl). The above MAX phase may be one or more MAX phases selected from the group consisting of titanium aluminum carbide (Ti3AlC2), titanium aluminum carbide (Ti2AlC), niobium aluminum carbide (Nb2AlC), vanadium aluminum carbide (V2AlC), molybdenum titanium aluminum carbide (Mo2TiAlC2), molybdenum gallium carbide (Mo2Ga2C), and mixtures thereof.
[0048] The above conductive polymer precursor solution may be a solution of one or more conductive polymer precursors selected from the group consisting of aniline (C6H5NH2), pyrrole (C4H5N), thiophene (C4H4S), and mixtures thereof.
[0049] The solvent of the transition metal dichalcogenide nanoflower, the MXene, the transition metal precursor, the chalcogen precursor, or the conductive polymer precursor is from the group consisting of water, N-methyl-2-pyrrolidone (NMP), toluene, benzene, tetrahydrofuran (THF), ethylene glycol, ethylene chloride, ethylene oxide, dimethylsulfoxide (DMSO), dimethylformamide (DMF), hydrochloric acid, sulfuric acid, acetic acid, phosphoric acid, methanol, ethanol, propanol, isopropanol, butanol, and mixtures thereof. It may be one or more selected solvents.
[0051] The present invention can be explained in detail below through manufacturing examples and experimental examples.
[0052] However, the following manufacturing examples and experimental examples are merely illustrative of the present invention, and the content of the present invention is not limited to the following manufacturing examples and experimental examples.
[0054] <Preparation Example 1> Preparation of transition metal dichalcogenide, conductive polymer, and MXene composite
[0055] <1-1> Preparation of Molybdenum Diselenide Nanoflowers
[0056] 0.0160 mol sodium molybdate (Sodium molybdate, Na2MoO2) in a mixed solvent of 40 ml of deionized water and 60 ml of ethanol 4·A sodium molybdate solution was prepared by dissolving 2H2O, Thomas Baker, purity-98%). A selenium solution was prepared by dissolving 0.0318 mol of selenium powder (Se, Thomas Baker, purity-98%) in 50 ml of hydrazine aqueous solution (Hydrazine hydrate).
[0057] The prepared sodium molybdate solution and the selenium solution were stirred for 30 minutes at a temperature of 40°C and a speed of 600 rpm, and then stirred for 1 hour at a temperature of 70°C and a speed of 600 rpm to prepare a homogeneous mixed solution.
[0058] The above mixed solution was transferred to an autoclave and treated at a temperature of 200°C for 24 hours, after which a precipitate was obtained by centrifuging at a speed of 7,000 rpm. The precipitate was washed with deionized water to remove impurities, vacuum dried at a temperature of 80°C for 24 hours, and ground with a mortar and pestle to produce molybdenum diselenide nanoflowers (MoSe2).
[0060] <1-2> Preparation of Molybdenum Diselenide / Polyaniline Complex
[0061] After adding 2 g of the molybdenum diselenide nanoflower (MoSe2) of Preparation Example <1-1> to 30 ml of deionized water, a MoSe2 dispersion solution was prepared by ultrasonizing at room temperature (28 ℃) for 2 hours.
[0062] An aniline mixed solution was prepared by stirring 2 ml of aniline, 5 ml of hydrochloric acid (HCl), and 32 ml of deionized water, and then refrigerated for 3 hours.
[0063] The above-mentioned chilled aniline mixed solution and the above-mentioned MoSe2 dispersion solution were mixed by stirring at a speed of 600 rpm, then transferred to an ice bath at 0 ℃, and a precipitate was obtained by stirring for 3 hours while adding 25 ml of ammonium persulfate (APS, 0.2 M) solution dropwise. The precipitate was thoroughly washed with deionized water and ethanol, vacuum dried at 50 ℃ for 5 hours, and ground with a mortar and pestle to prepare a molybdenum diselenide / polyaniline composite (MoSe2 / PANI). The amounts of the above-mentioned MoSe2 dispersion solvent and the above-mentioned aniline mixed solution added to prepare MoSe2 / PANI composites with different PANI contents are as shown in Table 1 below.
[0064] Complex name MoSe 2 dispersion solution aniline mixed solution MoSe2 / PANI_2wt% 30 ㎖ 19.5 ㎖ MoSe2 / PANI_4wt% 30 ㎖ 39.0 ㎖ MoSe2 / PANI_6wt% 30 ㎖ 58.0 ㎖
[0066] <1-3> Preparation of Molybdenum Diselenide / Polyaniline / Titanium Carbide MXene Composites
[0067] A suspension solution was prepared by adding 2 g of Ti3AlC2MAX phase to 24 ml of hydrofluoric acid (HF) and stirring, and the suspension solution was washed with deionized water until the pH reached 5 to 6. The washed suspension solution was centrifuged at 7,000 rpm to obtain a precipitate, and the precipitate was vacuum dried at 80 ℃ for 24 hours to obtain titanium carbide MXene (Ti3C2T x Prepared ).
[0068] An aniline mixed solution was prepared by stirring 1 ml of aniline, 3 ml of hydrochloric acid (HCl), and 16 ml of deionized water, and then refrigerated for 3 hours.
[0069] In 30 ml of deionized water, 1 g of molybdenum diselenide nanoflower (MoSe2) of Preparation Example <1-1> or 1 g of the titanium carbide MXene (Ti3C2T x After adding ) respectively, ultrasonic treatment was performed at 28 ℃ for 2 hours to obtain the MoSe2 dispersion solution and Ti3C2T xA dispersion solution was prepared. The above MoSe2 dispersion solution and the above Ti3C2T were mixed with the above aniline mixture solution. x After combining the dispersion solutions, they were transferred to an ice bath at 0°C and stirred at 600 rpm for 1 hour to prepare a homogeneous mixture. 12 ml of APS solution (0.2 M) was added dropwise to the mixture while stirring for 3 hours; a synthesis solution containing the synthesized complex was prepared by observing the mixture changing from black to dark green. The synthesis solution was filtered to separate the complex, and the separated complex was washed with deionized water and ethanol, vacuum dried at 50°C for 6 hours, and ground using a mortar and pestle to produce a molybdenum diselenide / polyaniline / titanium carbide MXene complex (MoSe2 / PANI / Ti3C2T x ) was manufactured. Ti3C2T x MoSe2 / PANI / Ti3C2T with different content x The above MoSe2 dispersion solvent mixed to prepare the complex, the above Ti3C2T x The amounts of the dispersion solution and the aniline mixed solution are as shown in Table 2 below.
[0070] Complex name MoSe 2 dispersion solution Ti 3 C 2 T x dispersion solution aniline mixed solution MoSe2 / PANI / Ti3C 2_ T x _4wt% 30 ㎖ 10 ㎖ 20 ㎖ MoSe2 / PANI / Ti3C 2_ T x _8wt% 30 ㎖ 20 ㎖ 20 ㎖ MoSe2 / PANI / Ti3C 2_ T x _12wt% 30 ㎖ 30 ㎖ 20 ㎖ MoSe2 / PANI / Ti3C 2_ T x _16wt% 30 ㎖ 40 ㎖ 20 ㎖
[0072] FIG. 2 is a schematic diagram showing a method for preparing a transition metal dichalcogenide, a conductive polymer, and a MXene composite of the present invention.
[0073] Referring to Figure 2(a), it was confirmed that transition metal dichalconide nanoflowers can be prepared by mixing a solution in which a metal precursor and a chalcogen precursor are uniformly mixed, synthesizing at high temperature, washing and vacuum drying, and then grinding with a mortar and pestle.
[0074] Referring to Figure 2(b), it was confirmed that a composite can be synthesized by mixing an ammonium persulfate (APS) solution with a solution in which a MXene dispersion solution and a transition metal dichalcogenide nanoflower dispersion solution are mixed in an aniline solution, and then the composite can be washed, vacuum-dried, and then ground with a mortar and pestle to produce a transition metal dichalcogenide, conductive polymer, and MXene composite powder.
[0076] <Preparation Example 2> Preparation of a resistive ammonia sensing electrode comprising a transition metal dichalcogenide, a conductive polymer, and a MXene complex
[0077] <2-1> Preparation of an electrode containing molybdenum diselenide nanoflowers
[0078] The surface of an interdigitated electrode (IDE) comprising 10 pairs of comb-shaped electrode fingers formed on a substrate with a width of 10 mm and a length of 10 mm, with a spacing of 50 μm between each finger, was sterilized with ethanol and dried at 60 ℃ for 1 hour to prepare.
[0079] A MoSe2 dispersion solution was prepared by adding 2 mg of the molybdenum diselenide nanoflower (MoSe2) of Preparation Example <1-1> to 150 µl of deionized water and stirring, and then the MoSe2 dispersion solution was applied to the IDE electrode for 1 minute, spin-coated at a speed of 4500 rpm, and dried at 80 ℃ for 30 minutes to prepare the MoSe2 electrode.
[0080] <2-2> Preparation of an electrode containing a molybdenum diselenide / polyaniline complex
[0081] A MoSe2 / PANI electrode was prepared in the same manner as in Preparation Example <2-1>, except that a MoSe2 / PANI composite (MoSe2 / PANI) of Preparation Example <1-2>, rather than the MoSe2 nanoflower (MoSe2) of Preparation Example <1-1>, was added to deionized water and stirred to prepare a MoSe2 / PANI dispersion solution, and then the MoSe2 / PANI dispersion solution was spin-coated onto the IDE electrode. The content of MoSe2 / PANI contained in the MoSe2 / PANI dispersion solution is as shown in Table 3 below.
[0082] Electrode names deionized water Types of input complexes MoSe 2 / PANI dispersion solution MoSe2 / PANI_2wt% electrode 0.15 ㎖ MoSe2 / PANI_2wt% 0.15 ㎖ MoSe2 / PANI_4wt% electrode 0.15 ㎖ MoSe2 / PANI_4wt% 0.15 ㎖ MoSe2 / PANI_6wt% electrode 0.15 ㎖ MoSe2 / PANI_6wt% 0.15 ㎖
[0084] <2-3> Preparation of an electrode containing a molybdenum diselenide / polyaniline / titanium carbide MXene complex
[0085] The molybdenum diselenide / polyaniline / titanium carbide MXene composite (MoSe2 / PANI / Ti3C2T) of Preparation Example <1-3>, rather than the molybdenum diselenide nanoflower (MoSe2) of Preparation Example <1-1> above. x Except for applying ) to the IDE electrode above, MoSe2 / PANI / Ti3C2T in the same manner as Preparation Example <2-1> above x An electrode was fabricated. MoSe2 / PANI / Ti3C2T contained in the above MoSe2 / PANI dispersion solution. x The content is as shown in Table 4 below.
[0086] Electrode names deionized water Types of input complexes MoSe 2 / PANI / Ti 3 C 2 T x dispersion solution MoSe2 / PANI / Ti3C 2_ T x _4wt% electrode 0.15 ㎖ MoSe2 / PANI / Ti3C 2_ T x _4wt% 0.15 ㎖ MoSe2 / PANI / Ti3C 2_ T x _8wt% electrode 0.15 ㎖ MoSe2 / PANI / Ti3C 2_ T x _8wt% 0.15 ㎖ MoSe2 / PANI / Ti3C 2_ T x _12wt% electrode 0.15 ㎖ MoSe2 / PANI / Ti3C 2_ T x _12wt% 0.15 ㎖ MoSe2 / PANI / Ti3C 2_ T x _16wt% electrode 0.15 ㎖ MoSe2 / PANI / Ti3C 2_ T x _16wt% 0.15 ㎖
[0088] <Experimental Example 1> Structural Analysis of Transition Metal Dichalcogenides, Conductive Polymers, and MXene Composites
[0089] <1-1> Analysis of the Crystal Structures of Transition Metal Dichalcogenides, Conductive Polymers, and MXene Composites
[0090] The crystal structure of the transition metal dichalcogenide, conductive polymer, and MXene composite of <Preparation Example 1> above was analyzed by X-ray diffraction (XRD).
[0092] Figure 3 is a graph showing the results of XRD analysis of the crystal structure of the transition metal dichalcogenide, conductive polymer, and MXene composite of the present invention.
[0093] Referring to FIG. 3, the molybdenum diselenide nanoflower (MoSe2) of Preparation Example <1-1>, the molybdenum diselenide / polyaniline composite (MoSe2 / PANI) of Preparation Example <1-2>, and the molybdenum diselenide / polyaniline / titanium carbide MXene composite (MoSe2 / PANI / Ti3C2T) of Preparation Example <1-3> xAs a result of comparative analysis of the crystal structure of ) using XRD, it was confirmed that the peak width widened as PANI was introduced into the above MoSe2 having a hexagonal crystal structure, and a peak at 9° occurred as MXene was introduced.
[0095] <1-2> Microstructural Analysis of Transition Metal Dichalcogenides, Conductive Polymers, and MXene Composites
[0096] The microstructure of the transition metal dichalcogenide, conductive polymer, and MXene composite of <Preparation Example 1> above was analyzed using a scanning electron microscope (SEM) and energy dispersive X-ray spectroscopy (EDS).
[0098] Figure 4 is an image showing the results of SEM analysis and EDS mapping of the microstructure of the transition metal dichalcogenide, conductive polymer, and MXene composite of the present invention.
[0099] Referring to Fig. 4(a), the structure of the molybdenum diselenide of Preparation Example <1-1> was analyzed by SEM, and it was confirmed that flower-shaped molybdenum diselenide nanoflowers (MoSe2) were formed. Additionally, referring to Fig. 4(b), the composition of the MoSe2 was confirmed by EDS mapping, and it was confirmed that Mo and Se were uniformly distributed.
[0100] Referring to Fig. 4(c), the structure of the molybdenum diselenide / polyaniline composite of Preparation Example <1-2> was analyzed by SEM, and it was confirmed that a molybdenum diselenide / polyaniline composite (MoSe2 / PANI) with increased surface roughness was formed by coating polyaniline (PANI) on the surface of MoSe2. Additionally, referring to Fig. 4(d), the composition of the MoSe2 / PANI was confirmed by EDS mapping, and it was confirmed that Mo, Se, N, O, and C were uniformly distributed.
[0101] Referring to FIG. 4(e), the structure of the molybdenum diselenide / polyaniline / titanium carbide MXene composite of Preparation Example <1-3> was analyzed by SEM, and the result showed that titanium carbide MXene (Ti3C2T x Molybdenum diselenide / polyaniline / titanium carbide MXene composite (MoSe2 / PANI / Ti3C2T) with increased surface roughness by coating the surface of ) with MoSe2 / PANI. x It was confirmed that ) is formed. Also, referring to Fig. 4(f), the above MoSe2 / PANI / Ti3C2T x As a result of confirming the composition through EDS mapping, it was confirmed that Mo, Se, N, O, Ti, F, and C are uniformly distributed.
[0103] <Experimental Example 2> Structural analysis of an ammonia sensing electrode comprising a transition metal dichalcogenide, a conductive polymer, and a MXene complex
[0104] The structure of the ammonia sensing electrode comprising the transition metal dichalcogenide, conductive polymer, and MXene complex of Preparation Example <2-3> above was analyzed using a Field-Emission Scanning Electron Microscope (FESEM).
[0106] Figure 5 is an image showing the results of analyzing the structure of an ammonia sensing electrode comprising a transition metal dichalcogenide, a conductive polymer, and a MXene complex of the present invention using FESEM.
[0107] Referring to FIG. 5, the molybdenum diselenide / polyaniline / titanium carbide MXene composite (MoSe2 / PANI / Ti3C2T) of Preparation Example <2-3> above x As a result of analyzing the cross-sectional structure of the electrode containing _12wt%) using FESEM, the MoSe2 / PANI / Ti3C2T on the surface of the interdigital electrode (IDE) x It was confirmed that the coating was dense and uniform with an average thickness of 751 nm.
[0109] <Experimental Example 3> Structural analysis of a resistive ammonia sensing electrode comprising a transition metal dichalcogenide, a conductive polymer, and a MXene complex
[0110] After placing the ammonia sensing electrode comprising the transition metal dichalcogenide, conductive polymer, and MXene composite of Preparation Example <2-3> above into the chamber of a gas sensing device, ammonia (NH3) gas was supplied to the chamber to verify the performance of the electrode.
[0112] FIG. 6 is a schematic diagram showing a gas sensing device comprising an ammonia sensing electrode comprising a transition metal dichalcogenide, a conductive polymer, and a MXene complex of the present invention.
[0113] Referring to FIG. 6, the molybdenum diselenide / polyaniline composite (MoSe2 / PANI) electrode of Preparation Example <2-2> or the molybdenum diselenide / polyaniline / titanium carbide MXene composite (MoSe2 / PANI / Ti3C2T) of Preparation Example <2-3> x ) An electrode is placed in a gas sensing chamber, and after supplying diluted NH3 gas prepared by mixing NH3 gas and air in a mass flow controller (MFC) to said chamber, the current-voltage (IV) is analyzed at a source meter connected to said electrode to the MoSe2 / PANI / Ti3C2T x The NH3 sensing ability of the electrode was confirmed.
[0115] Figure 7 is a graph showing the results of analyzing the ammonia gas sensing ability of an ammonia sensing electrode comprising a transition metal dichalcogenide, a conductive polymer, and a MXene complex of the present invention.
[0116] Referring to Fig. 7(a), when the MoSe2 / PANI electrodes of Preparation Example <2-2> with different concentrations of PANI were placed in the chamber under conditions of 1 V DC bias, room temperature (28 ℃), and atmospheric pressure, 1000 ppm of NH3 gas was supplied at 200 sccm and the change in resistance according to the exposure time was checked. As a result, it was confirmed that the MoSe2 / PANI electrode containing 4 wt% of PANI had a faster reaction rate with NH3 gas and a larger range of resistance change than the MoSe2 / PANI electrode containing 2 wt% or 6 wt% of PANI, thereby confirming that the NH3 gas detection performance is excellent.
[0117] Referring to Fig. 7(b), Ti3C2T x MoSe2 / PANI / Ti3C2T of Preparation Example <2-3> with different concentrations x As a result of supplying 1000 ppm NH3 gas at 200 sccm to a chamber with electrodes placed under a 1 V DC bias, room temperature (28 ℃), and atmospheric pressure, and checking the change in resistance according to exposure time, 12 wt% Ti3C2T x The above MoSe2 / PANI / Ti3C2T including x The electrode contains 4 wt%, 8 wt%, or 16 wt% Ti3C2T x The above MoSe2 / PANI / Ti3C2T including x It was confirmed that the reaction speed with NH3 gas is faster and the range of resistance change is larger than that of the electrode, thereby confirming that the NH3 gas detection performance is excellent. The NH3 gas detection values, reaction speed, and recovery speed of the above electrodes are as shown in Table 5 below.
[0118] Electrode names Detected value (R o / R g ) reaction rate Recovery speed Preparation Example <2-2> MoSe2 / PANI_2wt% 76.71 45.4 S 40.9 S MoSe2 / PANI_4wt% 534.39 19.6 S 22.0 S MoSe2 / PANI_6wt% 26.07 33.2 S 35.32 S Preparation Example <2-3> MoSe2 / PANI / Ti3C 2_ T x _4wt% 124.8 37.0 S 58.0 S MoSe2 / PANI / Ti3C 2_ T x _8wt% 999.2 8.6 S 34.6 S MoSe2 / PANI / Ti3C 2_ T x _12wt% 6481.1 4.7 S 18.4 S MoSe2 / PANI / Ti3C 2_ T x _16wt% 88.72 17.5 S 39.3 S
[0120] <Experimental Example 4> Analysis of Sensing Performance of a Resistive Ammonia Sensing Electrode Containing Transition Metal Dichalcogenide, Conductive Polymer, and MXene Composite
[0121] After placing the ammonia sensing electrode comprising the transition metal dichalcogenide, conductive polymer, and MXene composite of <Preparation Example 2> above in the chamber of a gas sensing device, ammonia (NH3) gas was supplied to the chamber to verify the performance of the electrode.
[0123] Figure 8 is a graph showing the results of a comparative analysis of the ammonia gas sensing performance of an ammonia sensing electrode comprising a transition metal dichalcogenide, a conductive polymer, and a MXene complex of the present invention.
[0124] Referring to FIGS. 8(a) to (c), the MoSe2 electrode of Preparation Example <2-1>, the MoSe2 / PANI_4wt% electrode of Preparation Example <2-2>, and the MoSe2 / PANI / Ti3C2T of Preparation Example <2-3> x As a result of supplying 1000 ppm NH3 gas at 200 sccm to the chamber, which was equipped with a 12 wt% electrode under conditions of 1 V DC bias, room temperature (28 ℃), and atmospheric pressure, and checking the change in resistance according to exposure time, the MoSe2 / PANI / Ti3C2T x It was confirmed that the _12wt% electrode has a faster reaction speed with NH3 gas and a larger range of resistance change than the above MoSe2 electrode and the above MoSe2 / PANI_4wt% electrode, thereby confirming that the NH3 gas detection performance is excellent.
[0125] Referring to FIGS. 8(a) to (d), the MoSe2 electrode, the MoSe2 / PANI_4wt% electrode and the MoSe2 / PANI / Ti3C2T x As a result of supplying 1000 ppm NH3 gas at 200 sccm to the chamber in which the _12 wt% electrode was placed and checking the reaction rate and recovery rate, the MoSe2 / PANI / Ti3C2T xIt was confirmed that the electrode has the best NH3 gas detection performance and recovery speed by confirming that it has a faster reaction speed with NH3 gas, a larger range of resistance change, and a faster resistance recovery speed than the MoSe2 electrode and the MoSe2 / PANI electrode. The NH3 gas detection values, reaction speeds, and recovery speeds of the electrodes are as shown in Table 6 below.
[0126] Electrode names Detected value (R o / R g ) reaction rate Recovery speed Preparation Example <2-1> MoSe2 77.53 27.9 S 59.9 S Preparation Example <2-2> MoSe2 / PANI_4wt% 834.39 19.6 S 22.0 S Preparation Example <2-3> MoSe2 / PANI / Ti3C 2_ T x _12wt% 6481.1 4.7 S 18.4 S
[0128] <Experimental Example 5> Performance Analysis of a Resistive Ammonia Sensing Electrode Containing Transition Metal Dichalcogenide, Conductive Polymer, and MXene Composite
[0129] After placing the ammonia sensing electrode comprising the transition metal dichalcogenide, conductive polymer, and MXene composite of Preparation Example <2-3> above into the chamber of a gas sensing device, the performance of the electrode was analyzed by supplying ammonia (NH3) gas, etc. to the chamber under conditions of a DC bias of 1 V, room temperature (28 ℃), and atmospheric pressure.
[0131] Figure 9 is a graph showing the results of a comparative analysis of the performance of an ammonia sensing electrode comprising a transition metal dichalcogenide, a conductive polymer, and a MXene complex of the present invention.
[0133] <5-1> Analysis of the Repeatability of Ammonia Sensing Electrodes
[0134] MoSe2 / PANI / Ti3C2T of Preparation Example <2-3> above x The repeatability of the electrode was verified by alternately supplying NH3 gas and air to the chamber in which the 12wt% electrode was placed.
[0135] Referring to FIG. 9(a), the MoSe2 / PANI / Ti3C2T of Preparation Example <2-3> above x As a result of checking the change in resistance after repeating a cycle of alternately supplying 1000 ppm NH3 gas and air at 200 sccm to the chamber with the _12 wt% electrode placed therein for 4 consecutive times, the MoSe2 / PANI / Ti3C2T xIt was confirmed that the NH3 gas detection performance is maintained by confirming that the resistance change range of the _12wt% electrode does not change significantly.
[0137] <5-2> Sensitivity Analysis of Ammonia Sensing Electrode
[0138] MoSe2 / PANI / Ti3C2T of Preparation Example <2-3> above x The sensitivity of the electrode was checked by supplying NH3 gas of various concentrations to the chamber in which the 12wt% electrode was placed.
[0139] Referring to FIG. 9(b), the MoSe2 / PANI / Ti3C2T of Preparation Example <2-3> above x When NH3 gas ranging from 1 ppm to 1000 ppm was supplied at 200 sccm to the chamber in which the 12wt% electrode was placed and the change in resistance was checked, it was confirmed that the NH3 gas of 1 ppm was detected, but as the concentration of the NH3 gas decreased, the magnitude of the decrease in resistance decreased proportionally.
[0140] Referring to FIG. 9 (c) and (d), the MoSe2 / PANI / Ti3C2T of Preparation Example <2-3> x NH3 gas at a concentration of 1 ppm to 1000 ppm was supplied to the chamber where the 12 wt% electrode was placed at a rate of 200 sccm, and the response according to each concentration was checked to confirm that there was excellent linearity between the concentration of NH3 gas and the response, and that it had a low detection limit of 0.6 ppm.
[0142] <Experimental Example 6> Selectivity Analysis of a Resistive Ammonia Sensing Electrode Containing Transition Metal Dichalcogenide, Conductive Polymer, and MXene Complex
[0143] After placing the ammonia sensing electrode comprising the transition metal dichalcogenide, conductive polymer, and MXene complex of Preparation Example <2-3> above into the chamber of a gas sensing device, various types of The selectivity of the electrode was verified by supplying an operating gas containing gas.
[0145] Figure 10 is a graph showing the results of analyzing the selectivity of an ammonia sensing electrode comprising a transition metal dichalcogenide, a conductive polymer, and a MXene complex of the present invention.
[0146] Referring to FIG. 10, the MoSe2 / PANI / Ti3C2T of Preparation Example <2-3> above x When operating gases including ammonia (NH3), carbon dioxide (CO2), formaldehyde (HCHO), nitrogen dioxide (NO2), methanol (CH3OH), ethanol (C2H5OH), acetone (CH3COCH3), and methane (CH4) were supplied at 200 sccm to the chamber in which a 12wt% electrode was placed, and the response according to each gas was checked, it was confirmed that the selectivity for NH3 gas was the highest.
[0148] In conclusion, the present invention provides a ternary complex of a transition metal dichalcogenide, a conductive polymer, and MXene, and a resistive ammonia sensing electrode comprising said ternary complex. The ternary complex is formed by preparing a MoSe2 dispersion solution by dissolving molybdenum diselenide nanoflowers (MoSe2) synthesized by hydrothermal synthesis in deionized water, and a titanium carbide MXene (Ti3C2T) formed by selectively etching an aluminum layer. x By dissolving ) respectively in deionized water, Ti3C2T x After preparing a dispersion solution, the MoSe2 dispersion solution and the Ti3C2T in a mixed solvent containing aniline x It is manufactured by introducing a dispersion solution and synthesizing it using an in situ oxidative polymerization method in the same reaction system. In addition, the resistive ammonia sensing electrode is manufactured by applying the composite to the electrode surface, spin-coating, and drying.
[0149] As a result of analyzing the crystal structure of the above ternary complex by XRD, the molybdenum diselenide nanoflower (MoSe2) and the molybdenum diselenide / polyaniline / titanium carbide MXene complex (MoSe2 / PANI / Ti3C2T x By confirming that the crystal structures of ) are different, polyaniline (PANI) and titanium carbide MXene (Ti3C2T x It was confirmed that the crystal structure changed when the element was introduced into the molybdenum diselenide (MoSe2). In addition, as a result of analyzing the microstructure of the composite using SEM and EDS mapping, it was confirmed that a composite with evenly distributed elements was formed.
[0150] As a result of analyzing the cross-section of the above-mentioned resistive ammonia sensing electrode using FESEM, it was confirmed that the composite was densely and uniformly coated.
[0151] As a result of verifying the performance of the above-described resistive ammonia sensing electrode, it was confirmed that the reaction rate with ammonia (NH3) gas is fast and the range of resistance change is large, thereby confirming excellent NH3 detection performance. Furthermore, it was confirmed that the resistive ammonia sensing electrode maintains its detection performance even after repeated cycles, has a low detection limit, and exhibits excellent ammonia selectivity.
Claims
Claim 1 An ammonia sensing sensor comprising: an electrode; and a sensing layer formed on the electrode; wherein the sensing layer comprises a ternary complex of a transition metal dichalcogenide, a conductive polymer, and MXene, wherein the transition metal dichalcogenide provides an adsorption active site for ammonia gas, the conductive polymer forms a charge transfer path between the transition metal dichalcogenide and the MXene to improve sensitivity, and the MXene improves electron mobility and active surface area to improve gas adsorption capacity and provides an efficient path for charge transfer. Claim 2 An ammonia detection sensor according to claim 1, wherein the electrode comprises a comb-shaped electrode finger. Claim 3 An ammonia sensing sensor according to claim 1, wherein the sensing layer is formed with a thickness of 200 nm to 1000 nm. Claim 4 An ammonia sensing sensor according to claim 1, wherein the ternary complex comprises 78 wt% to 90 wt% of the transition metal dichalcogenide, 2 wt% to 6 wt% of the conductive polymer, and 8 wt% to 16 wt% of the MXene. Claim 5 An ammonia sensing sensor according to claim 1, wherein the transition metal dichalcogenide is one or more transition metal dichalcogenides selected from the group consisting of molybdenum disulfide (MoS2), molybdenum diselenide (MoSe2), tungsten disulfide (WS2), and tungsten diselenide (WS2). Claim 6 An ammonia sensing sensor according to claim 1, wherein the conductive polymer is one or more conductive polymers selected from the group consisting of polyaniline (PANI), polypyrrole (PPy), polythiophene (PT), and mixtures thereof. Claim 7 In claim 1, the above MXene is titanium carbide MXene (Ti3C2T x ), niobium carbide MXene (Nb2CT x ), vanadium carbide MXene (V2CT x ) and molybdenum carbide MXene (Mo2CT x An ammonia sensing sensor, one or more MXenes selected from a group consisting of ). Claim 8 In claim 1, the ammonia detection sensor is an ammonia detection sensor having ammonia gas selectivity at room temperature. Claim 9 In claim 1, the ammonia detection sensor has a detection value (R) at room temperature. o / R g Ammonia detection sensor with ) ranging from 88.0 to 6500.
0. Claim 10 In claim 1, the ammonia detection sensor is an ammonia detection sensor having a reaction rate of 4.0 S to 18.0 S and a recovery rate of 18.0 S to 35.0 S at room temperature. Claim 11 In claim 1, the ammonia detection sensor is an ammonia detection sensor that detects ammonia of 0.6 ppm to 1000 ppm. Claim 12 In claim 1, the ammonia detection sensor is an ammonia detection sensor having a detection limit (LOD) of 0.6 ppm or higher. Claim 13 A method for manufacturing an ammonia sensing sensor, comprising: a step of preparing a ternary complex of a transition metal dichalcogenide, a conductive polymer, and MXene; a step of preparing a ternary complex dispersion solution by adding and stirring the ternary complex in a solvent; and a step of forming a sensing layer by coating the ternary complex dispersion solution onto an electrode. Claim 14 In claim 13, the step of preparing the ternary complex of the transition metal dichalcogenide, conductive polymer, and MXene comprises: a step of preparing a transition metal dichalcogenide nanoflower; a step of preparing a MXene; a step of preparing a transition metal dichalcogenide dispersion solution by adding and stirring the transition metal dichalcogenide nanoflower in a solvent; a step of preparing a MXene dispersion solution by adding and stirring the MXene in a solvent; a step of mixing the transition metal dichalcogenide dispersion solution and the MXene dispersion solution, and dropping and stirring a conductive polymer precursor solution; and a step of separating the complex by filtering the stirred solution; a method for preparing an ammonia sensing sensor. Claim 15 In claim 13, the step of preparing the transition metal dichalcogenide nanoflower comprises: a step of preparing a mixed solution by mixing a transition metal precursor solution and a chalcogen precursor solution; a step of separating a transition metal dichalcogenide nanoflower precipitate by centrifuging the mixed solution after reacting it at a high temperature; and a step of vacuum drying and grinding the precipitate; a method for manufacturing an ammonia sensing sensor. Claim 16 A method for manufacturing an ammonia sensing sensor according to claim 15, wherein the mixed solution is a solution in which 50 wt% to 80 wt% of the transition metal precursor solution and 20 wt% to 50 wt% of the chalcogen precursor solution are mixed. Claim 17 A method for manufacturing an ammonia detection sensor according to claim 13, wherein the step of manufacturing the MXene comprises: a step of preparing a suspension solution by adding and stirring a MAX phase in an acidic solvent; a step of neutralizing the suspension solution by washing; a step of separating the MXene precipitate by centrifuging the washed suspension solution; and a step of vacuum drying the MXene precipitate. Claim 18 A method for manufacturing an ammonia sensing sensor according to claim 13, wherein the stirred solution is a stirred solution comprising 20 wt% to 50 wt% of the transition metal dicalconide dispersion solution, 20 wt% to 50 wt% of the MXene dispersion solution, and 10 wt% to 40 wt% of the conductive polymer precursor solution.